Low‐dose and long‐term azithromycin significantly decreases Staphylococcus aureus in the microbiome of refractory CRS patients. Issue 2 (26th July 2020) - Renteria, Axel E.; Maniakas, Anastasios; Mfuna, Leandra Endam; Asmar, Marc‐Henri; Gonzalez, Emmanuel; Desrosiers, Martin
Abstract : Background: The sinonasal microbiome is believed to play an important role in the pathophysiology of refractory chronic rhinosinusitis (CRS). We evaluated changes in the microbiome following a 4‐month course of low‐dose azithromycin. Assessing microbiome alterations following such a treatment may help identify underlying mechanisms of this drug. Methods: A total of 48 adults with refractory CRS were enrolled in a double‐blind, randomized, placebo‐controlled trial. Patients were randomized to 250 mg of azithromycin or placebo 3 times weekly for 4 months. During this time, daily budesonide saline irrigations were continued. Sinonasal swabs were collected by endoscopically‐assisted method prior to treatment initiation and at the end of it, and sent for 16S ribosomal RNA gene sequencing. High‐resolution ANCHOR pipeline was used to infer and annotate putative species. The 2 patient groups were compared using DESeq2 differential abundance analysis. Results: From initiation to the end of azithromycin treatment, patients showed a significant difference in beta diversity analysis ( p = 0.0004) along with a significant decrease in 71 different operational taxonomic units (OTUs) of Staphylococcus aureus (false discovery rate [FDR] < 0.05) obtained from the differential abundance analysis. This was not observed in placebo‐treated patients. By the end of treatments, azithromycin‐treated patients had a significant decrease in 29 different OTUs of S. aureus (FDR < 0.05) when compared to placebo. Conclusion: A 4‐month course of 250 mg of azithromycin 3 times weekly in patients with refractory CRS significantly decreases S. aureus abundance in the sinonasal microbiome. Considering the pathogenic role of S. aureus in the refractory CRS population, azithromycin may constitute an additional therapeutic option to help control this disease.